Construction of recombinant pseudorabies virus expressing PCV2 Cap, PCV3 Cap, and IL-4: investigation of their biological characteristics and immunogenicity - Yang, Yanting; Xu, Zhiwen; Tao, Qian; Xu, Lei; Gu, Sirui; Huang, Yao; Liu, Zheyan; Zhang, Yang; Wen, Jianhua; Lai, Siyuan; Zhu, Ling (Frontiers in Immunology, 2024)
Backgound: Porcine circovirus type 2 (PCV2) is a globally prevalent and recurrent pathogen that primarily causes slow growth and immunosuppression in pigs. Porcine circovirus type 3 (PCV3), a recently discovered virus, commonly leads to reproductive disorders in pigs and has been extensively disseminated worldwide. Infection with a single PCV subtype alone does not induce severe porcine circovirus-associated diseases (PCVD), whereas concurrent co-infection with PCV2 and PCV3 exacerbates the clinical manifestations. Pseudorabies (PR), a highly contagious disease in pigs, pose a significant threat to the swine industry in China.Methods: In this study, recombinant strains named rPRV-2Cap/3Cap and rPRV-2Cap/3Cap/IL4 was constructed by using a variant strain XJ of pseudorabies virus (PRV) as the parental strain, with the TK/gE/gI genes deleted and simultaneous expression of PCV2 Cap, PCV3 Cap, and IL-4. The two recombinant strains obtained by CRISPR/Cas gE gene editing technology and homologous recombination technology has genetic stability in baby hamster syrian kidney-21 (BHK-21) cells and is safe to mice. Results: rPRV-2Cap/3Cap and rPRV-2Cap/3Cap/IL4 exhibited good safety and immunogenicity in mice, inducing high levels of antibodies, demonstrated 100% protection against the PRV challenge in mice, reduced viral loads and mitigated pathological changes in the heart, lungs, spleen, and lymph nodes during PCV2 challenge. Moreover, the recombinant viruses with the addition of IL-4 as a molecular adjuvant outperformed the non-addition group in most indicators.Conclusions: rPRV-2Cap/3Cap and rPRV-2Cap/3Cap/IL4 hold promise as recombinant vaccines for the simultaneous prevention of PCV2, PCV3, and PRV, while IL-4, as a vaccine molecular adjuvant, effectively enhances the immune response of the vaccine.